1979
DOI: 10.1097/00000658-197910000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Duct Fistula and Renal Transplantation

Abstract: Thoracic duct drainage (TOO) was established for 21-115 days in 40 kidney recipients with an average removal per patient day of 4.7 I lymph and 1.88 billion cells. Cellular and humoral immunity were depressed. TOO and immunosuppressive drugs were started at transplantation in 35 recipients of cross-match negative grafts. Althougb the results were better than in precedent non-TOO controls, eight patients rejccted their ~~rafts before a full TOO effect, and three of the eight developed predominantly anti-B lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Although these leukocytes are thought to be mostly sessile cells, there is evidence that tissue macrophages can leave the stroma by reverse transmigration and are indeed found in efferent lymph (34,35). Therefore, these cells can be envisioned to play an important role in carrying mucosal Ags into distant tissues such as synovium.…”
Section: Discussionmentioning
confidence: 99%
“…Although these leukocytes are thought to be mostly sessile cells, there is evidence that tissue macrophages can leave the stroma by reverse transmigration and are indeed found in efferent lymph (34,35). Therefore, these cells can be envisioned to play an important role in carrying mucosal Ags into distant tissues such as synovium.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, more than 500 patients have been treated with this method (2,3). In all species, liver allografts are rejected less aggressively than allografts of other organs (4-6), probably because Ia antigens are less prominent on liver cells than on cells of other organs.…”
mentioning
confidence: 99%
“…Kidney graft survival was not significantly altered by 3 weeks of TDD but was doubled after 6 and 9 weeks. As in humans [19][20][21], this timing of therapeutic effect was out of phase with the T-Iymphocyte count, which was depressed almost immediately after TDD and remained low thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…In Gowans' original rat experiments [7] and with long-term external TDD in humans [18][19][20][21], humoral and cellular immunity were both depressed. This duality was controversial at the time of the human trials because at that time a pure cell-mediated effect was expected or reported by some investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation